THE RELATIONSHIP BETWEEN SELF-ESTEEM AND POST-POWER SYNDROME IN ELDERLY RETIREMENT IN THE ELDERLY POSYANDU JATIREJO VILLAGE, NGANJUK REGENCY - Oktora Wilda, Lexy; Puspitasari, Citra Ayu Dwi (SYNTIFIC, 2024)
Background. The aging process is a natural stage of human life, and one of the phases faced by the elderly is retirement. Retirement often triggers anxiety, fear, and other psychological symptoms, known as Post-Power Syndrome. The purpose was to determine the relationship between self-esteem and Post-Power Syndrome in the elderly during retirement. Research Method. This research used a correlational study with a Cross-Sectional design. This research was conducted in July 2024 at the Elderly Posyandu Jatirejo Village, Nganjuk Regency. The sample size was 35 respondents, inclusion criteria are elderly ?60 years old, have not worked for ?1 year, are cooperative, healthy, and do not have physical disabilities. The independent variable is self-esteem and the dependent variable is Post-Power Syndrome in the elderly. Collecting data on self-esteem with Post-Power Syndrome elderly using a questionnaire sheet. Statistical tests using Spearman rank with a significant ? ? 0.05. Findings. Based on the results of research from 35 respondents, most of them showed high self-esteem, namely 19 respondents (54.3%) and 18 respondents (51.4%) experienced mild Post-Power Syndrome. The results of the Spearman rank correlation test show a p-value of 0.012, and r= -0.42 as moderate and negative correlation which means that there is a relationship between self-esteem and Post-Power Syndrome in the Elderly Retirement Period. Conclusion. The higher self-esteem felt by the elderly will decrease the Post Power Syndrome experienced. Appropriate psychological and social interventions in this regard are essential to improve the self-esteem and psychological well-being of the elderly in retirement.